2017
DOI: 10.1556/030.64.2017.041
|View full text |Cite
|
Sign up to set email alerts
|

Does subinhibitory concentrations of clinically important antibiotic induce biofilm production of Enterococcus faecium strains?

Abstract: Biofilm structures are the most resistant form of active microorganisms against sanitation, disinfection, and sterilization processes. One of the specific properties of biofilm is the development of antibiotic resistance that can be up to 1,000-fold greater than planktonic cells. Enterococcus faecium is a human pathogen that causes nosocomial bacteremia and at the present time, it is well known that most of the chronic infections are biofilm-based. Recent evidence suggested that subinhibitory concentrations (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
5
0
2
Order By: Relevance
“…Norfloxacin demonstrated a significant increase in the growth of biofilm at 1/4 MIC and resulted in did not increase biofilm formation isolated SS_9801, SS_1886 and SS_595 at 1/8 and 1/16 MIC compared to the untreated norfloxacin. Some studies have strongly shown that the sub-MIC antibiotic can promote biofilm formation (Yuksel et al, 2018;Sato et al, 2018;Rachid et al, 2000). Our research brings clear evidence that sub-MICs of norfloxacins enhance the ability of S. suis to form biofilms.…”
Section: Biofilm Formation Of Sub-mic Norfloxacinsupporting
confidence: 60%
See 1 more Smart Citation
“…Norfloxacin demonstrated a significant increase in the growth of biofilm at 1/4 MIC and resulted in did not increase biofilm formation isolated SS_9801, SS_1886 and SS_595 at 1/8 and 1/16 MIC compared to the untreated norfloxacin. Some studies have strongly shown that the sub-MIC antibiotic can promote biofilm formation (Yuksel et al, 2018;Sato et al, 2018;Rachid et al, 2000). Our research brings clear evidence that sub-MICs of norfloxacins enhance the ability of S. suis to form biofilms.…”
Section: Biofilm Formation Of Sub-mic Norfloxacinsupporting
confidence: 60%
“…Antibiotics are still the most effective measures in controlling bacterial pathogens. However, antibiotics are usually used at sub-MIC (Minimum Inhibitory Concentration) doses to prevent infection (Yuksel et al, 2018). The concentration of antibiotics in feed are often lower than the MIC in the treatment of infections (Adamowicz et al, 2018;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…További vizsgálatok szükségesek annak eldöntésére is, hogy a helyi érzéstelenítők szubinhibitoros koncentrációja az antibiotikumokhoz hasonlóan befolyásolja-e a kórokozók adherenciáját, ami az infekció kialakulásának meghatározó lépése [20,21].…”
Section: áLtalános Jellemzőkunclassified
“…The total amount of antibiotics mixed into pig medicated feed in 2017 is estimated to be 843 tons [ 9 ]. Although the total amount of antibiotics used on farms is significant, due to the low oral absorption rate, irregular medication, and illegal use of low-dose antibiotic growth promoters, antibiotics often exist in livestock and poultry at sub-inhibitory concentration levels [ 10 ], which leads to prolonged disease and treatment difficulties. Oral antibiotic powders (Amoxicillin, lincomycin, oxytetracycline, doxycycline, gentamicin, and Tylosin, etc.)…”
Section: Introductionmentioning
confidence: 99%